PENYUSUNAN MATERI INTERPERSONAL SKILL (KEMAMPUAN BERINTERAKSI ANTAR INDIVIDU) KELAS X6 SMA NEGERI 5 PEKANBARU TAHUN AJARAN 2013/2014 - Widianti, Suro; Saam, Zulfan; Asyari, Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The title of this research is "Compilation Of Matter Interpersonal Skills (Ability Interacting Between Individuals) Class X6 SMA N 5 Pekanbaru AcademicYear 2013/2014". This study aims at the formulation of matter on interpersonal skills necessary for high school students in terms of the clarity of the material, the material systematics, image support, and the adequacy of the material. Before the researchers gave the material to students, researchers first showed the results of the material to the supervisor I and II, one of the lecturers BK, teachers and tutors where researchers do research peers as much as 6 people. After passing through many revisions along with the suggestions by the experts further provides materials researchers interpersonal skills in schools where the researcher is doing, in providing this material as much as 3x the meeting where after researchers provide teaching materials andstudentmaterialspemberikan interpersonal skillassessment of the material provided. From the values given by the experts and the students gain calculation results for material gain clarity aspect value of 4.44 which includes categories Very clear, systematic aspects of the material to obtain the value of 4.43 which includes categories Very Systematic, to support aspects of the image to get the value 4.06 A category that includes, for the renewal of the material aspects of obtaining the value of 4.61 which includes the category of Most Recently, to obtain material sufficiency aspect value of 4.68 which includes the category of Most Complete, whereas for all aspects of assessment materials indicate that the materials developed already meet the criteria expected by the acquisition value of 4.44 which includes the category of Very Good.Keywords: Matter Interpersonal Skill.WISUDA OKTOBER